On Finding Dexamine thea (Amphipoda, Dexaminidae) in Ukrainian Territorial Waters (Crimea, Black Sea) - Grintsov, V.A. (Вестник зоологии, 2010)
Dexamine thea Boeck, 1861 (Amphipoda, Dexaminidae), the rare species never registered in the territorial waters of Ukraine, was first found in Laspi Bay, 40 km of Sevastopol (Crimea, Black Sea). 200 amphipods were examined and described. The pictures showing specific morphological characters are given. Sex and size structure of the community and characteristics of the biotope are discussed. Исследованы особи Dexamine thea Boeck, 1861 (Amphipoda, Dexaminidae), ранее не отмечавшиеся в территориальных водах Украины. Вид зарегистрирован в районе б. Ласпи (Крым, ЮБК, 40 км от Севастополя). Исследовано 200 особей. Приведены рисунки характерных морфологических признаков. Получены характеристики поселений — половой состав, размерная структура. Приведены данные о биотопе обитания D. thea.